A critical review: The dialogue of Filipino American faculty in higher education - Edward Joaquin (Adult Education Research Conference, 2014)
The purpose of this study is to illuminate the tenure experiences of Filipino American faculty in U.S. colleges and universities, exploring how race, gender, and their cultural influences have impacted their respective journeys.